2005
DOI: 10.1111/j.1440-1746.2005.03886.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of lamivudine administration according to Child class in patients with decompensated cirrhosis

Abstract: Long-term administration of LAM for patients with decompensated cirrhosis is effective. Earlier LAM administration in Child class B patients led to improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…A small study showed that patients of Child class B needed shorter time to achieve a 2-point reduction in CTP score (5.9 vs. 14 months, p <0.001) and to gain a 0.5 g/dl increment in albumin (5.8 vs. 14 months) than patients of Child class C [43]. These results suggest that patients with decompensated cirrhosis should receive antiviral therapy as early as possible to allow a better chance of functional recovery.…”
Section: Lamivudinementioning
confidence: 96%
“…A small study showed that patients of Child class B needed shorter time to achieve a 2-point reduction in CTP score (5.9 vs. 14 months, p <0.001) and to gain a 0.5 g/dl increment in albumin (5.8 vs. 14 months) than patients of Child class C [43]. These results suggest that patients with decompensated cirrhosis should receive antiviral therapy as early as possible to allow a better chance of functional recovery.…”
Section: Lamivudinementioning
confidence: 96%
“…54 This study was conducted in patients with e antigen-negative disease in which immuneinduced HBeAg seroconversion is not an option; therefore, the benefit of therapy is from the direct antiviral effect of the drug. Indeed, a decrease in viral load through antiviral therapy has been associated with histologic improvement, 26,27,[55][56][57][58][59][60][61] increased survival of patients with decompensated liver disease from hepatitis B, [62][63][64][65][66][67][68][69][70] and improved clinical outcome in patients with HBV reactivation following chemotherapy. 50,52,[71][72][73][74][75][76][77][78][79][80][81] Our analyses are conservative in the following aspects.…”
mentioning
confidence: 99%
“…Di Marcov first reported the clinical effect of LAM treatment with 59 cases of HBV-related cirrhosis (45 child-Pugh with A and 4 with B), showing that a sustained suppression of HBV DNA significantly improved the prognosis of patients with liver cirrhosis (Di Marco et al, 2005). Bae reported that 58.2% of patients show complete antiviral responses using LAM in decompensated HBV-related cirrhosis, which can improve the clinical prognosis (Bae et al, 2005). However, the failure of antiviral treatment or drug resistance are dangerous factors for liver disease progression and increase the incidence of liver cancer (Yeh et al, 2011;Zoulim, 2011).…”
Section: Et Al 2269mentioning
confidence: 99%
“…To date, the reasons and mechanisms of the different clinical outcomes after HBV infection are still unknown. Substantial clinical evidence shows that the differences in clinical outcomes after HBV infection might be related to HBV DNA level, antiviral treatment response, and immune activation (Ohishi and Chayama, 2012;Di Marco et al, 2005;Bae et al, 2005). All guidelines for the prevention and treatment of chronic hepatitis B both in China and in other countries clearly state that the main aim of treatment for chronic hepatitis B is to bring down the incidence rate and death rate of liver cirrhosis and liver cancer, to prolong life and to improve living conditions (Tujios and Lee, 2012; European Association for the Study of the Liver, 2012).…”
Section: Et Al 2269mentioning
confidence: 99%